2017
DOI: 10.1111/acel.12594
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decline in BubR1 impairs adult hippocampal neurogenesis

Abstract: SummaryAging causes significant declines in adult hippocampal neurogenesis and leads to cognitive disability. Emerging evidence demonstrates that decline in the mitotic checkpoint kinase BubR1 level occurs with natural aging and induces progeroid features in both mice and children with mosaic variegated aneuploidy syndrome. Whether BubR1 contributes to age‐related deficits in hippocampal neurogenesis is yet to be determined. Here we report that BubR1 expression is significantly reduced with natural aging in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 6 publications
5
36
0
Order By: Relevance
“…Other aneuploidogenic conditions include mosaic variegated aneuploidy syndrome, which is caused by a mutation in (a) a mitotic checkpoint component BubR1/Bub1B (type 1); (b) CEP57, which encodes a centrosomal protein (type 2) (Snape et al, ); or (c) TRIP13, which is involved in mitotic checkpoint complex silencing via Mad2 liberation (Alfieri, Chang, & Barford, ; Kaisari et al, ). A reduction in BubR1 protein in mice (BubR1 H/H mice) resulted in a systemic and neuronal progeria condition (Choi et al, ) and in impairment of adult hippocampal neurogenesis (Yang et al, ). The progeric conditions were partly ameliorated by targeted elimination/reduction of p16INK4‐positive cells (Baker et al, ), by enhancing Wnt signaling via loss of Dickkopf‐1 (Seib et al, ) or via inhibition of secreted frizzled‐related protein 3 (sFRP3) (Cho et al, ), both of which are endogenous Wnt antagonists.…”
Section: The “Amyloid‐beta Accumulation Cycle”mentioning
confidence: 99%
“…Other aneuploidogenic conditions include mosaic variegated aneuploidy syndrome, which is caused by a mutation in (a) a mitotic checkpoint component BubR1/Bub1B (type 1); (b) CEP57, which encodes a centrosomal protein (type 2) (Snape et al, ); or (c) TRIP13, which is involved in mitotic checkpoint complex silencing via Mad2 liberation (Alfieri, Chang, & Barford, ; Kaisari et al, ). A reduction in BubR1 protein in mice (BubR1 H/H mice) resulted in a systemic and neuronal progeria condition (Choi et al, ) and in impairment of adult hippocampal neurogenesis (Yang et al, ). The progeric conditions were partly ameliorated by targeted elimination/reduction of p16INK4‐positive cells (Baker et al, ), by enhancing Wnt signaling via loss of Dickkopf‐1 (Seib et al, ) or via inhibition of secreted frizzled‐related protein 3 (sFRP3) (Cho et al, ), both of which are endogenous Wnt antagonists.…”
Section: The “Amyloid‐beta Accumulation Cycle”mentioning
confidence: 99%
“…BubR1 −/+ mice showed mitotic slippage in the cells and were colon cancer‐prone (Dai et al., 2004; Rao et al., 2005), and BubR1 H/H hypomorphic mice were identified as a model for premature aging (Baker et al., 2004). Neuronal cell division and axon growth were inhibited by siRNA‐mediated BubR1 knockdown in the mouse brain (Yang et al., 2017). The above findings in BubR1 transgenic models led to a hypothesis that mitotic errors and CIN facilitate AD‐like neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Aging is known to result in significant reductions in hippocampal neurogenesis and cognitive dysfunction. We previously reported that BubR1 H/H mice exhibited impaired hippocampal neurogenesis (Yang et al, ). Therefore, we examined whether inhibition of sFRP3 could mitigate reduced neurogenesis in BubR1 H/H mice.…”
Section: Introductionmentioning
confidence: 96%
“…Mutant mice producing low levels of BubR1 ( BubR1 H/H mice) exhibit smaller brain sizes and were rescued by constitutive overexpression of BubR1, suggesting that brain development is mediated through BubR1 (Supporting Information Figure ). In addition, BubR1 H/H mice exhibit reduced hippocampal neurogenesis and impaired myelination (Choi et al, ; Yang et al, ). Together, these findings suggest that decreased BubR1 expression with aging contributes to brain dysfunction.…”
Section: Introductionmentioning
confidence: 99%